Pendekatan Munasabah Psikologiah Muhammad Ahmad Khalafullah: Analisis Kisah Luth dan Kaumnya dalam Al-Qur’an - Thoriqul Aziz; Ahmad Zainal Abidin (Asosiasi Ilmu Alqur'an dan Tafsir se-Indonesia, 2019)
One of the most important ways the Koran uses to convey the messages of God is to use stories. In the Qur’an, the mention of stories fulfills a quarter of the number of verses; there are recorded 1,453 to 1,600 verses. One of the stories in the Koran is the story of Lut and his people. The purpose of the present story is as a guide, warning, threat to humans. But some commentators have been ‘fascinated’ by revealing the reality of historical events, thus leaving the essence of the meaning contained. Khalafullah, in contrast to the others, tried to study the stories in the Koran by using literary methods. In his method, he revealed a psychological muna>sabah between stories and the conditions of the prophet or society when the Qur’an was revealed. This research found that, according to Khalafullah, the stories used by the Koran as an effective way to attract the interest and attention of Muslims at that time; found the relationship between the story of Lut and his people with the psychological condition of the Prophet and his followers, and there is a relation between the story of Lut and the psychological atmosphere of the Prophet’s opponents at that time. This research reinforces the theory that the context of the Prophet and his people when the Qur’an was revealed is a very important element to consider as someone tries to understand the message of the Qur’an.